Enhancing Speaking Skills through Comic Strips in the Seventh Grade Students of SMP Negeri 1 Surabaya - Aldaka, Femailia; Susanto, Fajar; Suparman, Suparman (JET ADI BUANA, 2023)
This study aims to investigate the improvement in students' speaking skill after implementing comic strips as a learning media. The subjects of this study were seventh grade students at SMP Negeri 1 Surabaya, totaling 35 students in a class. This research was a Classroom Action Research (CAR) which was carried out in two cycles. The researcher conducted the Pre-Cycle before implementing the comic strip. There were four phases carried out in cycle 1 and cycle 2: planning, action, observation, and reflection. The difference occurred in the implementation of cycle 2. Observation and speaking practice tests were two methods the researchers used to collect data in this study. The KKM in English subjects at SMP Negeri 1 Surabaya is 85. The results of this study showed that there were 10 students, or 28.5% of students, who achieved test scores above the KKM. In cycle 1, there were 23 students, or 65.7% of students, who passed the KKM, and in cycle 2 there were 30 students, or 85.7% of students in class VII B, who scored above the KKM. Thus, comic strips are effective in improving students' speaking skills.